Comparison of Interactions Between Soy Protein Isolate and Three Folate Molecules: Effect on the Stabilization, Degradation, and Oxidization of Folates and Protein - Linlin He; Yuqian Yan; Dandan Song; Shuangfeng Li; Yanna Zhao; Zhuang Ding; Zhengping Wang (Foods)
This study selected three approved folate sources—folic acid (FA), L-5-methyltetrahydrofolate (MTFA), and calcium 5-methyltetrahydrofolate (CMTFA)—to explore their interaction mechanisms with soy protein isolate (SPI) through spectrofluorometric analysis and molecular docking simulations. We investigated how these interactions influence the structural and physicochemical stability of folates and SPI. Three folates spontaneously bound to SPI, forming complexes, resulting in a decrease of approximately 30 kJ·mol−1 in Gibbs free energy and an association constant (Ka) of 105 L·mol−1. The thermodynamic parameters and molecular docking study revealed the unique binding mechanisms of FA and MTFA with SPI. FA’s planar pteridine ring and conjugated double bonds facilitate hydrophobic interactions, whereas MTFA’s reduced ring structure and additional polar groups strengthen hydrogen bonding. Although the formation of SPI–folate complexes did not result in substantial alterations to the SPI structure, their binding has the potential to enhance both the physical and thermal stability of the protein by stabilizing its conformation. Notably, compared with free FA, the FA-SPI complexes significantly enhanced FA’s stability, exhibiting 71.1 ± 1.2% stability under light conditions after 9 days and 63.2 ± 2.6% stability in the dark after 60 days. In contrast, no similar effect was observed for MTFA. This discrepancy can be ascribed to the distinct degradation pathways of the Fa and MTFA molecules. This study offers both theoretical and experimental insights into the development of folate-loaded delivery systems utilizing SPI as a matrix.